2013
DOI: 10.1142/s0192415x13500493
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture for Chronic Constipation: A Systematic Review

Abstract: This study was to evaluate the efficacy and safety of acupuncture for chronic functional constipation. Randomized controlled trials were searched in several databases. The primary outcome was a change in the number of weekly spontaneous bowel movements. The secondary outcomes included colonic transit activity, effective rate, Cleveland Clinic Score, and health-related quality of life score. Meta-analysis was done by using RevMan 5.1. After strict screening, 15 RCTs were included, containing 1256 participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 23 publications
1
50
1
2
Order By: Relevance
“…(10) and solving the set of Eqs. (11)(12)(13)(14) simultaneously, the four parameters of statistical parton model, T, V, µ u and µ d can be computed at desired energy scales which can be related to the S G values at some available energy scales, quoted in [17,18]. In Ref.…”
Section: Energy Dependence Of Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) and solving the set of Eqs. (11)(12)(13)(14) simultaneously, the four parameters of statistical parton model, T, V, µ u and µ d can be computed at desired energy scales which can be related to the S G values at some available energy scales, quoted in [17,18]. In Ref.…”
Section: Energy Dependence Of Parametersmentioning
confidence: 99%
“…Then by putting the final results in the sum rules, given by Eqs. (11,12) and Eq. (14), we can obtain the unknown parameters µ u , µ d and T by solving simultaneously the related set of equations.…”
Section: Statistical Approach and The Quark Modelmentioning
confidence: 99%
“…However, few studies have examined the effectiveness of acupuncture by comparing it to dietary fiber, laxatives, or prokinetic agents . A recent systematic reviews concluded that acupuncture for CFC was safe and might be as effective as conventional medical therapy in improving weekly spontaneous bowel movements, quality of life, and relevant symptoms . However, the low quality of the included trials in the review made the results inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…3 A systematic review on acupuncture in 1256 patients with chronic constipation reported that acupuncture increased the frequency of spontaneous bowel movements each week and was as effective as conventional drug therapy. 5 Another study of 1075 patients with refractory constipation showed that electroacupuncture, in which an electric current is applied to acupuncture needles inserted into the body, was effective for treatment. 6 The researchers noted that in previous studies on the effects of acupuncture, relatively intense stimulation was applied by inserting acupuncture needles (filiform needles) deep into the tissue up to the muscles.…”
Section: Introduction Bmentioning
confidence: 99%